Assessment of minimal residual disease in acute myeloid leukemia. - Grimwade, D; Vyas, P; Freeman, S (2010)
PURPOSE OF REVIEW: The last 15 years have witnessed significant improvements in technologies to detect minimal residual disease (MRD) in acute myeloid leukemia (AML). We review recent studies highlighting the potential for novel and standardized assays to provide independent prognostic information and develop more personalized treatment approaches. RECENT FINDINGS: Progress includes establishment of optimized real-time quantitative PCR (RQ-PCR) assays for WT1 (commonly overexpressed and a putative therapeutic target) and mutant NPM1 genes. Moreover, sequential MRD monitoring using an internationally standardized PML-RARA RQ-PCR assay has been successfully used to guide molecularly targeted therapy in acute promyelocytic leukemia (APL). There have also been significant advances in multiparameter flow cytometry (MFC) to detect MRD, with introduction of 6-10 color technology and improved understanding of the immunophenotype of leukemic stem cells. SUMMARY: Sensitive MRD detection using MFC and/or RQ-PCR has become feasible in virtually all AML patients. MRD monitoring is now considered a standard of care in APL. Recent studies provide a strong rationale for prospective trials investigating the merits of extending MRD detection to alter therapy and potentially improve outcome in other AML subtypes.